Intention to Utilize Mobile Game-Based Learning in Nursing Education from Teachers’ Perspective: A Theory of Planned Behavior Approach - U., Jhansi Rani; S. , Sireesha; Sweenie J, Edna; P. , Anusha; S. , Maha Lakshmi (International Journal of Psychosocial Rehabilitation, 2020)
When faced with a pandemic such as coronavirus disease 2019 (COVID-19), many educational institutions are scrambling to find methods to enhance their present processes and prepare for the difficulties of this worldwide danger.. It’s not apparent whether nursing professors are ready to employ ICTs like video games to lessen the bad impacts of the epidemic, despite advice from experts. To find out more about nursing instructors’ behavioural purpose to use mobile game-based learning (MGBL) and its connection to key elements of the Theory of Planned Behavior, this research was conducted" (i.e., perceived behavioural control, subjective norms, and attitude). Most of the nursing instructors were female, a master’s degree holder, with an academic rank of instructor, not a certified professional teacher, and a permanent and fulltime employee at private institutions in the Visayas area of the Philippines, according to descriptive data. As a result, they have little knowledge about MGBL or mobile games in general. As a final note, we found that characteristics associated with Theory of Planned Behavior were positively connected with nursing educators’ plans to use MGBL. Predicting whether or not nursing instructors would use MGBL in the classroom is the subject of future research, which builds on the work done here by exploring the potential benefits of MGBL in nursing education.